Bottleneck Congestion and Modal Split Revisited - Romeo Danielis; Edoardo Marcucci (Fondazione Eni Enrico Mattei (FEEM), 1999)
The paper examines the efficiency of alternative road pricing schemes when an alternative railroad service is available. The paper uses a model, developed by Tabuchi (1993), in which road transport presents a bottleneck congestion technology while railroad transport shows economies of scale with respect to the number of train users. The competition between the two modes is assumed to be on cost basis only. It is found that if the railroad fare is set equal to the average cost, the relative efficiency of the regimes depends on parameters' values. The numerical simulation shows that the fine toll regime is generally to be preferred to the alternative regimes but when the fixed railroad cost is large enough so that the inefficient exploitation of the scale economies is less than compensated by the toll revenue.
Keywords: R41; 330; Road transport; Public transport; Congestion; Congestion pricing